MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII C SMP NEGERI 6 BANJARMASIN PADA MATERI KIMIA BAHAN MAKANAN DENGAN MODEL PEMBELAJARAN BILINGUAL PREVIEW REVIEW BERBASIS INKUIRI 5E - Muhammad Nor Huda; Bambang Suharto; Muhammad Kusasi (Universitas Lambung Mangkurat, 2015)
Abstract. This study aims to improve students' critical thinking skills class VIII C SMP Negeri 6 Banjarmasin bilingual learning through inquiry-based 5E preview review. This research is a classroom action research that consists of four phases: planning, implementation, observation, and reflection. The subjects were students of class VIII C. While the object of study is the overall chemical process and learning outcomes with the implementation of bilingual teaching inquiry-based 5E preview review to improve critical thinking skills. Instrument in the form of test and observation sheets. Analysis using qualitative descriptive analysis. The experiment was conducted in two cycles with six sessions by applying bilingual teaching inquiry-based 5E preview review. The results showed that the application of bilingual teaching inquiry-based 5E preview review the steps include: Engagement, exploration, explanation, elaboration and evaluation can improve students' critical thinking skills. In the first cycle gained critical thinking skills class VIII C is 57.25% with low qualifications. Obtained through the second cycle students' critical thinking skills class VIII C on the second cycle of 75.25% with medium qualifications. Critical thinking skills of students increased from cycle I to cycle II of 31.44%.Keywords: critical thinking skills, inquiry-based bilingual preview review 5E